SHOULD INDONESIA LEAVE THE FREE TRADE AGREEMENT? - Himawan Yusuf; Setiyono Nugroho (Unit Penerbitan Politeknik Keuangan Negara STAN, 2022)
The main purpose of the government joining the free trade agreement (FTA) is to increase domestic production and exports. Providing cheap or even free tariffs to other countries, of course, expect the same thing when we export to that country along with the loss of import duty revenue. This study aims to examine whether tariffs along with other variables affect exports. The data used is export-import unbalanced panel data from 2017 to 2020 which is divided based on the classification of business fields. The method is using regression by random effect model. The test results show that the tariffs have no significant effect on increasing exports. In aggregate, Indonesia does not benefit from trade with FTA’s countries. The government needs to evaluate unfavorable agreements and provide stimulus to increase production capacity so as not to lose the benefits of the free trade agreement. The success of other FTA such as the growth of Gross Domestic Product of household consumption is not measured in this study.